PDF LAJU PERTUMBUHAN POHON JELUTUNG RAWA (Dyera lowii HOOK.F) DISADAP DAN TIDAK DISADAP Growth Rate of Tapped and Untapped Swamp Jelutung (Dyera Lowii Hook.F) : LIES INDRAYANTI, SOSILAWATY, JOHANNA M. A. ROTINSULU - journal journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThis research aims to identify first, the difference of Jelutung’s growth rate in two different peatthickness. Second, This research aims to identify the difference between tap and untapped Jelutung’sgrowth rate. Observation material consist of tapped 18 Jelutung trees in the thickness of 4,00 m and6,00 m, 9 untapped Jelutung trees in 4,00 m thickness. The measurement of diameter accretion isconducted consistently during 12 months. In every thickness point in the peatland, soil is taken as asample to analyse the soil features. This research uses Factorial Randomized Group Design, wherethe first research target is conducted with two different peatland thickness and three diameter class oftrees, while for the second research target is conducted to both tapped and untapped trees and threedifferent diameter class. Each treatment is conducted three times.Tha varian analysis result shows that peatland thickness has significantly influence on jelutunggrowth rate, while tree diameter has insignificant influence. Tapped jelutung that is planted on 4mthickness has 37-57% higher in terms of growth rate compare to that is planted on 6m thickness. Weconjecture that due to the peatland condition, the regression and correlation analysis on 4 peatlandfeatures shows significant different with strong correlation where the moisture level, pH (KCL), Ca totaland Fe total.The varian analysis shows that tapping has a significant influence on jelutung growth rate.Tapped jelutung has 36-49% lower compare to untapped jelutung. Jelutung growth rate based onpeatland thickness and tapping is higher compare to the growth rate of other trees such as meranti,ramin and rimba (based on peatland thickness) in the same location.Keywords: Peat depth, growth rate, tap